A scoping review of medical practice variation research within the informatics literature. (September 2022) - Sohn, Sunghwan; Moon, Sungrim; Prokop, Larry J.; Montori, Victor M.; Fan, J. Wilfred
Highlights: The informatics discipline has made modest contributions to MPV research during 1995–2021, without exhibiting maturity of treating MPV as a prime area of investigation. There were few informatics studies on how MPV affected patient outcomes and few on generating knowledge from the MPV. Medical practice variation (MPV) is a significant issue in both clinical practice and research. MPV has been a well-established subject in health services research and appears to have caught the attention of some informatics researchers. Abstract: Rationale: We performed a scoping review of informatics core literature about medical practice variation (MPV) as an agile summary of the subject in our field. Materials and methods: The Ovid integrated database was searched between 1946 and 2022 to identify MPV studies published in major informatics journals and conference proceedings. Two reviewers performed relevance screening, with assistance from another independent reviewer for adjudication. The included articles were then thematically analyzed and summarized through discussion among all three reviewers. Results: A total of 43 articles were included and went through the thematic analysis. About half (n = 21) of the included articles were published in conference proceedings. Five articles reported the effect of MPV on patient outcomes. The variation of interest was most frequently in treatment decisions. In terms of the role informatics played (multiple roles allowed), 39 (90.7%) articles pertained to detection of MPV, 5 were about prevention of MPV and 4 about learning from MPV. Discussion: MPV remains a critical issue in health care, yet most informatics research has been focused on simple tasks such as automating the detection of MPV and assessing compliance to decision-support systems, and less focused on addressing the causes of variation or supporting learning from variation. Conclusion: Our scoping review found that informatics studies have focused on detecting of MPV, especially variability in treatments and deviation from practice guidelines. Technological advances should promote more informatics research focused on explaining and learning from MPV.